Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1096/fj.01-0036com
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan serves a novel role in airway mucosal host defense

Abstract: Enzymes secreted onto epithelial surfaces play a vital role in innate mucosal defense, but are believed to be steadily removed from the surface by mechanical actions. Thus, the amount and availability of enzymes on the surface are thought to be maintained by secretion. In contrast to this paradigm, we show here that enzymes are retained at the apical surface of the airway epithelium by binding to surface-associated hyaluronan, providing an apical enzyme pool 'ready for use' and protected from ciliary clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
86
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 43 publications
(52 reference statements)
10
86
0
Order By: Relevance
“…Options include direct secretion from the airway epithelium, airway smooth muscle cells, goblet cells, mucus glands, or a combination of these. Among these options, the direct secretion from the airway epithelium and airways smooth muscle cells are the most likely, and several studies have demonstrated the ability of the epithelium and airways smooth muscle cells to secrete HA in vitro (3,37,38). The relatively negative staining of HA in goblet cell and mucous gland cell populations indicates that these cells are less likely to be involved in the secretion of HA into the airway lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Options include direct secretion from the airway epithelium, airway smooth muscle cells, goblet cells, mucus glands, or a combination of these. Among these options, the direct secretion from the airway epithelium and airways smooth muscle cells are the most likely, and several studies have demonstrated the ability of the epithelium and airways smooth muscle cells to secrete HA in vitro (3,37,38). The relatively negative staining of HA in goblet cell and mucous gland cell populations indicates that these cells are less likely to be involved in the secretion of HA into the airway lumen.…”
Section: Discussionmentioning
confidence: 99%
“…HA is a major component and important constituent of the extracellular matrix (2,3). In asthma, studies have linked HA levels in the bronchoalveolar lavage fluid (BAL) with inflammation and have been shown to increase after histamine challenge (4,5).…”
mentioning
confidence: 99%
“…RHAMM is not only a modulator of growth factor receptor, but also has major roles in progression and proliferation of various types of cancer (9,11). RHAMM has been found in a variety of mammalian cells, including smooth muscle cells, endothelial cells, nerve cells, macrophages, spermatozoa (12,13), and certain types of tumor cell, including prostate (14), breast (15) and gastric (16) cancer, and B-cell chronic lymphocytic leukemia (17). However, whether the upregulation of RHAMM contributes to hepatocarcinogenesis of HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that HA plays an important role in the processes of wound healing and repair of mucosal surfaces; the presence of mucosal ulcers increase the expression of HA receptors, which provides a ligand for cell adhesion. HA binds to and interacts with the hyaluronic acid-mediated motility [14]. Patients with chronic bronchitis and recurrent exacerbations treated with HA have seen reduce the number of exacerbations, with less need for antibiotic therapies to control recurrent episodes [15].…”
Section: Introductionmentioning
confidence: 99%